Modern Dzikir and Spiritual Crisis - Iim Suryahim; Uus Putria; Muslim Muslim (UIN Sunan Gunung Djati Bandung, 2020)
Modern humans are more likely to be known as materialists and far from spiritual values. This study aims to determine the relationship of the Qur'an's spirituality in overcoming the spiritual crisis of modern human life. This research uses qualitative methods or literature review. The results of this study indicate that in some studies, modern humans who are closer to the Qur'an are mainly those who practice Dzikir to live more mature spiritually. Keywords: Al-Qur'an, Dzikir, Spiritual Crisis.